Trilha sonora: da tv ao Youtube, mediações narrativas na telenovela Passione - Ledo, João Paulo Fagundes (2012)
The objective of this dissertation is to present a reception research carried out by relating the sound track of the soap opera Passione(RedeGlobo), the digital platform youtube.com, and the creation of musical narrative, through the appropriation of the internet by holdings through the cracks, gave us verify how some relations ships are mediated by the media in cyberspace, and the reports and discussions of internet source of primary analytical work, where the cultural matrix of a cultural product, especially melodrama, are evidenced by possibility of emerging digital. The research is based on theoretical British Cultural Studies, especially in the figure of Raymond Williams, in addition to studies concerning Latin American School, where work and the theory of mediation of Jesus Martin-Barbero were used as main reference forthe topic discussed here, references as well as Michel de Certeau on appropriations. Alson in this context, the work of Pierre Lévy and Henry Jenkins about cyberspace, cyber culture and convergence culture, were used by the prospect of understanding how the new digital presents on the internet with the creation of digital narratives